Students’ Perceptions of the Use of Local Folklore in Narrative Text - Istiqomah, Sri Ayu; Oktarini, Widya; Laeli, Anita Fatimatul (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2025)
This study explores students' in-depth perceptions of the use of folklore in narrative text learning, considering the lack of studies discussing this topic. This study employed a qualitative approach with a case study design, conducted at SMA Negeri Arjasa Jember. The research participants consisted of five tenth graders who were selected purposively based on two criteria: having adequate verbal communication skills to express their thoughts and having previous learning experiences related to the use of folklore in narrative texts in English lessons. Data were collected through interviews and analyzed using data reduction, data presentation, and conclusion-drawing techniques by Miles & Huberman. The results showed that students had a positive perception of the integration of folklore, which was considered to improve motivation, engagement, understanding of local culture, and mastery of contextual language. However, limited vocabulary and difficulty in comprehending English structure still pose an obstacle to achieving mastery of past tenses in English. These findings open up opportunities for further research that examines the effectiveness of scaffolding strategies in helping students overcome linguistic gaps when learning narrative texts based on local culture.